2018
DOI: 10.3892/ijmm.2018.3973
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of midazolam on focal cerebral ischemia in rats through anti‑apoptotic mechanisms

Abstract: Stroke is a cerebrovascular circulatory disorder and its high mortality rate represents a prominent threat to human health. Subsequent apoptosis and cytotoxicity are the main causes underlying the poor prognosis. Midazolam (MdZ) is a benzodiazepine drug that is clinically used during surgical procedures and for the treatment of insomnia, with a potential ability to treat stroke. The protective effect of MdZ was investigated on glutamate-induced cortical neuronal injuries in vitro and transient middle cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Western blot performed on brain extracts of mice, rats or humans showed that the AB177487 detects two bands at 45–50 kDA. It has been widely used to label neurons in rat (H. Yu,Wang, et al 2019) or mouse brain slices (Joy et al, 2019; Saito et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Western blot performed on brain extracts of mice, rats or humans showed that the AB177487 detects two bands at 45–50 kDA. It has been widely used to label neurons in rat (H. Yu,Wang, et al 2019) or mouse brain slices (Joy et al, 2019; Saito et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Inducing sedation by enhancing the activity of the GABA A receptor is quite common in stroke patients and it is only sensible to ask whether this pharmacological manipulation could potentially have any detrimental effects on neuronal viability in this setting, especially since literature data are controversial regarding this matter [62][63][64]. It has also been suggested that benzodiazepines may be neuroprotective when given soon after stroke, but harmful when administered during late recovery [63].…”
Section: Enhancing Gaba a Activation Using Isoguvacine Does Not Influmentioning
confidence: 99%
“…Totally, 68 out of them (36.8 %) have been confirmed with anti-stroke effects by in vivo , in vitro or other literature evidence ( Supplementary Table 3 ). Taking midazolam for example, abundant research indicated that midazolam exerted beneficial effects on focal cerebral ischemia in rats via anti-apoptotic mechanisms [39] . Diazepam was also demonstrated to reduce brain lesion size in a photothrombotic rat model of focal ischemia [40] .…”
Section: Resultsmentioning
confidence: 99%